Antioxidant Effects of Temulawak and Black Cumin Honey in Stunted Children: A Study in Cirebon - Siti Pandawangi TW; Akrom Akrom; Nurkhasanah Nurkhasanah; Ahmad Azrul Zuniarto (Journal of Public Health and Pharmacy, 2025)
Introduction: The imbalance between the production of free radicals and the antioxidant defense system in the body will cause the body to experience oxidative stress. This can be caused by chronic malnutrition. In children, this condition causes growth and development failure called stunting. Honey, temulawak and black cumin are herbs with high antioxidant content, formulated in one preparation to test its effectiveness. The purpose of the study was to determine specific descriptions experienced by stunted children and to test the antioxidant effectiveness of preparation temulawak-black cumin honey. Methods: The research method used was quasi-experimental, pre-post design, the research time starts from January-May 2023. The population of Stunting children in the Tegalwangi locus area, Cirebon Regency, the selected samples or subjects are children aged 24-60 months who meet the inclusion criteria. The subjects were divided into 2 groups, namely the treatment group that received the test preparation for 4 months and the control group without the provision of the test preparation. Blood sampling was carried out simultaneously or simultaneously at the village hall with the help of trained analysts. The antioxidant parameters superoxide dismutase, catalase, glutathione peroxidase and free radical parameters Nitric oxide and malondialdehyde. The data obtained will be analysed using an independent t-test. Results: The results of the study on 50 stunted children showed low levels of Superoxide Dismutase, Catalase, Glutathione peroxidase, and free radical parameters Nitric oxide and Malondialdehyde were obtained high. This means that stunted children experience oxidative stress. There was significant antioxidant effectiveness with increased levels of SOD and Catalase in the treatment group (P<0.05), a decrease in NO and MDA in the treatment group (P<0.05) compared to the control group. Conclusion: Temulawak-black cumin honey preparation has activity to reduce oxidative stress in stunted children in Cirebon.